Wing shape and migration in shorebirds: a comparative study. (4th April 2015) - Minias, Piotr; Meissner, Włodzimierz; Włodarczyk, Radosław; Ożarowska, Agnieszka; Piasecka, Anna; Kaczmarek, Krzysztof; Janiszewski, Tomasz
Abstract : Migration is an energetically expensive and hazardous stage of the annual cycle of non‐resident avian species, and requires certain morphological adaptations. Wing shape is one of the morphological traits that is expected to be evolutionarily shaped by migration. Aerodynamic theory predicts that long‐distance migrants should have more pointed wings with distal primaries relatively longer than proximal primaries, an arrangement that minimizes induced drag and wing inertia, but this prediction has mostly been tested in passerine species. We applied the comparative method of phylogenetically independent contrasts to assess convergent evolution between wing shape and migration within shorebirds. We confirmed the assumption that long‐distance migrants have less rounded wings than species migrating shorter distances. Furthermore, wing roundedness negatively correlates with fat load and mean distance of migratory flights, the basic components of migration strategies. After controlling for interspecific differences in body size, we found no support for a link between wing length and migration, indicating that wing shape is a more important predictor of shorebird migratory behaviour than wing length. The results suggest that total migration distance and migratory strategy may simultaneously act on the evolution of wing shape in shorebirds, and possibly in other avian species.